Peran Kepala Sekolah dalam Pemberdayaan Guru Honorer di SMPN 1 Umpu Semenguk Way Kanan - Ismail, Benhur; Putra, Ansori Dasa; Purwito, Teguh; Rosidah, Nur; Salamun (Lentera: Jurnal Ilmiah Kependidikan, 2025)
This study aims to analyze the role of school principals in empowering honorary teachers at SMPN 1 Umpu Semenguk Way Kanan, focusing on planning and implementation strategies, forms of empowerment, supporting and inhibiting factors, and honorary teachers' perceptions of the effectiveness of the principal's role. The study employs a qualitative approach with a case study design through data collection techniques including semi-structured in-depth interviews, passive participant observation, and documentation study involving the principal, honorary teachers, and vice principal for curriculum affairs. Data analysis uses the Miles and Huberman interactive model with stages of data reduction, data display, and conclusion drawing, while data validity is tested through source triangulation and technique triangulation. The results show that the principal's strategy is implemented systematically through comprehensive needs analysis integrated into the School Work Plan (RKS) and School Activity and Budget Plan (RKAS), with short-term program implementation (in-house training, workshops, clinical supervision, mentoring) and long-term programs (facilitation of further studies, certification assistance, internal career paths). Forms of empowerment encompass three dimensions: professional through inclusion in training/seminars, internal IHT/KKG, and benchmarking visits; structural/managerial through assignment of coordinator/homeroom teacher responsibilities to 50% of honorary teachers, involvement in decision-making, and autonomy in developing lesson plans; and psychological/motivational through non-financial rewards, creation of fair work climate, and personal coaching/mentoring approaches.